FISCAL EFFECTS OF UKRAINE’S CUSTOMS POLICY IN THE CONDITIONS OF INTEGRATION PROCESSES - Melnyk, V. M.; Rudenko , V. V.; Yevtushenko , N. M. (The actual problems of regional economy development, 2024)
In today's realities, in the conditions of the development of integration processes, Ukraine's active entry into the world economy and the general liberalization of foreign trade, the formation and implementation of customs policy remains an important task in the context of obtaining fiscal effects. To ensure economic recovery and growth, it is necessary to implement a customs policy that enables effective regulation of foreign economic activity, while at the same time ensuring stable receipts of customs payments to the state budget. Therefore, it is necessary to pay attention to the fiscal effects of the customs policy in the conditions of entry into the European and world trade and economic space. The article is devoted to the study of current issues of the formation and implementation of the customs policy of the state, the analysis of the consequences of the functioning of customs unions and the justification of fiscal effects for Ukraine and EU member states within the borders of the EU customs union. The specifics of the scientific tasks that are the subject of the research required the use of a set of special methods, the application of which helped to determine the content of customs policy, to consider the specifics of its implementation in the context of integration, in particular, when joining customs unions, as well as to assess the fiscal effects of the customs policy of Ukraine and its member countries EU, which have a common customs union. The article examines the concept of “customs policy” from the standpoint of legislators and scientists, substantiates its author's definition. The development of customs policy in the context of the development of integration processes is considered. Advantages and disadvantages of functioning of customs unions are considered. As a result of the study, it was proved that in Ukraine with the beginning of the entry into the free trade zone with the EU and in the EU member states upon joining the EU customs union, there was an increase in customs payments to the budget with the prevailing effect of "creating" trade. The latter consists in the fact that after the formation of the customs union and the abolition of import duties, when foreign goods from the union countries become cheaper than domestic ones, and consumers buy imported goods instead of domestic ones, the flow of imported goods arises and expands, so the resources of the integration union are used more efficiently and growing customs payments to the budget.